Structural Markedness in Formal Features: Deriving Interpretability - Bejar, Susana (Revue québécoise de linguistique)

(untitled) (Université du Québec à Montréal, 2000)
ABSTRACTThis paper argues that the internal structure of formal features plays an important role in the syntax and can account for complex surface phenomena which are otherwise difficult to explain. The hierarchical representation of morphosyntactic features developed in Harley 1994, Ritter 1997 and Harley and Ritter 1998 is incorporated into minimalist checking theory (Chomsky 1998). It is proposed that feature interpretability can be understood as a condition on configurations licensed by the feature geometry. Two principles governing the interaction between feature structure and core syntactic operations are proposed. The first stipulates that only structurally marked features may satisfy a probe. The second permits checking between non-identical features if they are in an implicational relation. Agreement asymmetries in Georgian and Standard Arabic are examined and are shown to be derived from the aforementioned principles.